2021
DOI: 10.1371/journal.pone.0255305
|View full text |Cite
|
Sign up to set email alerts
|

Subjects develop tolerance to Pru p 3 but respiratory allergy to Pru p 9: A large study group from a peach exposed population

Abstract: Peach tree allergens are present in fruit, pollen, branches, and leaves, and can induce systemic, respiratory, cutaneous, and gastrointestinal symptoms. We studied the capacity of peach fruit/Pru p 1, Pru p 3, Pru p 4, Pru p 7 and peach pollen/Pru p 9 for inducing symptoms following oral or respiratory exposure in a large group of subjects. We included 716 adults (aged 21 to 83 y.o.) exposed to peach tree pollen and fruit intake in the study population. Participants completed a questionnaire and were skin test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…To our best knowledge, this is the first systematic review and meta‐analysis to comprehensively summarize the relationships between pollen exposure and asthma exacerbation, as assessed through various respiratory outcomes with strict methodological concerns. The existing literature collected in a recent review of the respiratory health burden attributable to short‐term exposure to pollen had already suggested evidence of an association between outdoor pollen concentrations and most of the asthma outcomes we considered, especially in people with pre‐existing respiratory diseases 3–139 . Our overall meta‐analysis, subgroup analysis, and publication bias assessment confirm that a relationship between pollen exposure and asthma exacerbation exists but this require additional research due to its heterogeneity.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…To our best knowledge, this is the first systematic review and meta‐analysis to comprehensively summarize the relationships between pollen exposure and asthma exacerbation, as assessed through various respiratory outcomes with strict methodological concerns. The existing literature collected in a recent review of the respiratory health burden attributable to short‐term exposure to pollen had already suggested evidence of an association between outdoor pollen concentrations and most of the asthma outcomes we considered, especially in people with pre‐existing respiratory diseases 3–139 . Our overall meta‐analysis, subgroup analysis, and publication bias assessment confirm that a relationship between pollen exposure and asthma exacerbation exists but this require additional research due to its heterogeneity.…”
Section: Discussionsupporting
confidence: 54%
“…Horticulturists and fruit tree workers can develop occupational respiratory allergic diseases (rhinoconjunctivitis and asthma) 35 . Teranishi et al 46 conducted an epidemiological study on pollinosis among Japanese pear orchard workers and found positive skin tests (SPT) in 5.4% of them. Jiang et al 47 described a case of occupational allergy to peach ( Prunus persica ) pollen in an artificial pollination worker.…”
Section: State Of Artmentioning
confidence: 99%
“…In our cohort we did not find a significant difference in terms of clinical presentation in those positive for Pru p 4, similarly to other studies 23 . However, the rates of sensitization to profilins are low in some areas such as Spain or South Italy 22 , 24 , thus preventing to fully evaluate this aspect that should be further investigated.…”
Section: Discussionmentioning
confidence: 99%